IDENTITAS DIALEK BANYUMASAN SEBAGAI KONSTRUKSI BUDAYA STUDI PENGGUNAAN DIALEK BANYUMASAN DI KALANGAN PENUTUR ASLI BANYUMAS YANG BERADA DI SEMARANG - Gatikasari Mujiastuti; Turnomo Rahardjo (Interaksi Online, 2023)
The Banyumas dialect (ngapak) as a cultural identity has begun to experience a shift among native Banyumas speakers who live in Semarang City. This research tries to explore the identity negotiation process that is carried out, in which migrants experience a process of cultural construction, namely acculturation and cultural assimilation due to contact with the people of Semarang. This study aims to describe the identity negotiations carried out by native Banyumas speakers towards the Banyumasan dialect in their daily interactions in their environment in maintaining regional identity. This study also aims to determine the communication understanding of Banyumas native speakers who do not use their local dialect. This research is a qualitative research that uses a constructivism paradigm with a descriptive approach. The theory used is the Identity Negotiation Theory put forward by Stella Ting-Toomey. The results of this study were obtained through interviews with 6 informants who were native Banyumas migrants living in Semarang. In addition, the research results were also obtained from direct observation activities conducted by researchers at the research location, namely Semarang. The results of this study indicate that Banyumas native speakers in their daily interactions prefer to use contemporary dialects to be able to adapt and communicate with new environments. The informants in this study indicated that there was an effort to maintain the Banyumasan dialect as their original cultural identity. However, on the other hand, informants who moved from their place of origin tried to make adjustments, especially in terms of language and dialect. This adjustment was made to make it easier for them to communicate and minimize communication barriers. The Banyumasan dialect is still maintained, among others, when the informant is in a communication situation, talking with friends from Banyumasan who are in Semarang, college friends who already know the informant and family at home. There are informants who intentionally slip in Banyumasan dialects so that their friends can learn from them. There is also a situation where formal events are infiltrated by informants about the local Banyumasan dialect. The response of the Semarang people is that the Banyumasan dialect is funny and strange, but the people of Semarang are quite familiar with this dialect.